Condições sócio-econômicos em crianças vivendo em famílias afetadas pelo HIV/AIDS em estados do nordeste brasileiro - Cavalcante, Maria do Socorro (2012)
This study explores the relationships among demographic, socioeconomic and health status of children and adolescents whose parents were HIV positive or died due to the condition in the State of Ceará and Salvador, Bahia; Explore the relationships among the cities of Fortaleza and Salvador through the multiple correspondence analysis. We conducted a cross-sectional, multicenter, exploratory study, in reference services for HIV / AIDS in the State of Ceará and the city of Salvador. The study population consisted of HIV+ adults who answered a structured questionnaire about children under 13 years of both sexes, whose parents were HIV / AIDS in the period June 2008 to March 2009. Recruitment of participants took place in the outpatient clinic, in the hospital, or during the delivery of drugs for AIDS. We used Multiple Correspondence Analysis (MCA), as implemented in the software SPAD (Portable Système pour l'Analyse des données). This analysis enabled us to identify relationships among a large number of variables simultaneously. The proportion of HIV- infected children in Fortaleza was 14.2%, and 61.4% (27/44) of these had progressed to AIDS. In Salvador 34.7% of children were HIV+ and 95% (83/87) were diagnosed with AIDS. In multiple correspondence analysis visualized in Fortaleza: mother and father HIV+ (39.2%), children cared for by the mother and by relatives (54.8%), family income between 1 to 3 minimum salaries (55.1%), head of the family with up to three years of education (29.2%), socioeconomic class B (4.7%), children with age-appropriate academic year and sharing a room with more than 4 people (5.8%). In Salvador there were children that the mother was infected and no information about the dad (53.8%), mothers aged 35 years and older (39.6%), orphaned of father (11.3%), education of the head of the family between 4-7 years of education (48.4%) and socioeconomic class C (35.0%), children between 8-12 years of age (57.8%), children with non age-appropriate academic year and health status as excellent (60.7%). The most important factors that emerged from the study were city and serostatus of the child. These two active variables accounted for 75.3% of the variance. Results described the complex of socioeconomic variables closely associated with these families, and the complex and multiple epidemics of HIV, discrimination and poverty associated with these AIDS affected families.